(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article discusses the significance of fairy tales and riddles in fostering children’s creative thinking. These resources are found to be instrumental in shaping children’s speech, spirituality, worldview, and creativity. Uzbek folk tales, in particular, are known to instil in the young generation such qualities as diligence, creativity, generosity, nobility and patriotism.